Correction: CTL–doxorubicin (DOX)–gold complex nanoparticles (DOX–AuGCs): from synthesis to enhancement of therapeutic effect on liver cancer model. Issue 21 (14th October 2022) - Liu, Qiqian; Liu, Hui; Sacco, Pasquale; Djaker, Nadia; Lamy de la Chapelle, Marc; Marsich, Eleonora; Li, Xiaowu; Spadavecchia, Jolanda
Abstract : Correction for 'CTL–doxorubicin (DOX)–gold complex nanoparticles (DOX–AuGCs): from synthesis to enhancement of therapeutic effect on liver cancer model' by Qiqian Liu et al., Nanoscale Adv., 2020, 2, 5231–5241. ; https://doi.org/10.1039/D0NA00758G .